Aperçu de la situation de l’enseignement de l’aragonais à travers les voix de ses protagonistes - Iris Orosia Campos Bandrés; Rosa Tabernero Sala (Lengas)
Despite the fact that the academic year 2022/2023 marked a quarter of a century since the introduction of Aragonese in schools in Huesca, its situation in the school context is still far from being close to educational normalisation. Based on the research carried out over the last decade by the ECOLIJ group (Educación Comunicativa y Literaria en la Sociedad de la Información. Literatura Infantil y Juvenil en la construcción de identidades) of the University of Zaragoza, this paper presents a state of the question on the situation of the Aragonese language in the stages of Infant, Primary, Secondary and Baccalaureate Education based on the voices of different agents of the educational community. The research reviewed reveals a complex situation in which the scarce impact of school teaching on the creation of new speakers and the relevance of factors linked to contact with the language in the construction of favourable attitudes and representations towards the language and its teaching stand out.